Potential of quantitative flow ratio in guiding conduit selection between radial artery and saphenous vein graft for coronary artery bypass graftingCentral MessagePerspective - Chunyuan Wang, MD; Meice Tian, MD; Yang Wang, PhD; Lei Song, MD; Zhihui Hou, MD; Sipeng Chen, MS; Wei Feng, MD; Yan Zhang, MD; Zhan Hu, MD (JTCVS Open)
Objectives: Radial artery grafts and saphenous vein grafts exhibit heterogeneous responses to competitive flow, a phenomenon assessable through quantitative flow ratio. The present study aims to compare the patency of radial artery and saphenous vein grafts across various quantitative flow ratio ranges. Methods: The clinical data and quantitative flow ratio values for each target vessel were retrospectively collected in patients receiving radial artery or conventional saphenous vein grafts in our center from 2017 to 2021. The primary outcome was graft occlusion assessed by coronary computed tomography angiography and coronary angiography, and the secondary outcome was major adverse cardiac or cerebrovascular events. Mixed-effect multivariable Cox regression models were used to assess the independent effect of graft conduit type and quantitative flow ratio on graft occlusion. Results: A total of 1314 patients with 292 radial artery target vessels and 1736 saphenous vein graft target vessels were included. The median follow-up duration was 3 years. Quantitative flow ratio value of 0.57 was identified as the optimal threshold. Compared with saphenous vein graft, the radial artery exhibited lower patency in target vessels where quantitative flow ratio was greater than 0.57 (adjusted hazard ratio, 4.63, 95% CI, 2.61-8.21, P < .001), but higher patency in vessels in which the quantitative flow ratio was 0.57 or less (adjusted hazard ratio, 0.14, 95% CI, 0.03-0.68, P = .015). Conclusions: Radial artery grafts may achieve superior patency in target vessels with low quantitative flow ratio values, whereas saphenous vein grafts may be associated with higher short-term patency in vessels with higher quantitative flow ratio values.